(untitled) (Revista de Ensino em Artes, Moda e Design, 2022)
This article seeks to reflect on the ways of dressing and adorning the working women who circulated through the streets of Belém during the 20th century, using reproductions of pictorial works by artists from Pará Carlos de Azevedo, Antonieta Santos Feio and Andrelino Cotta as a support. The reproductions form the basis of the analysis of the specificities of such modes, which are crossed with textual sources from books and scientific articles. The themes of the use of images in the History of Fashion and Clothing research, decolonial fashion, the presentation of the Amazonian locus, a brief overview of women’s work in the 20th century in Belém do Pará are discussed, followed by the analysis of the clothing practices of Amazonian workers, based on the categories of washerwomen, greengrocers and street vendors, and, finally, harlots. It is important to emphasize that even in the face of deprivation, these women materialized, in their clothing and body adornments, the social signs of their professions, demonstrating that the concern with appearance was also present in all layers.